2001
DOI: 10.1346/ccmn.2001.0490605
|View full text |Cite
|
Sign up to set email alerts
|

Microtextures and the Origin of Muscovite-Kaolinite Intergrowths in Sandstones of the Utrillas Formation, Basque Cantabrian Basin, Spain

Abstract: Abstract--Muscovite-kaolinite intergrowths found in Albian sandstones of the Basque Cantabrian basin (northern Spain) were studied by optical, scanning and electron microscopy and electron microprobe analysis. Kaolinitization begins at grain edges, forming the characteristic fanned-out textures, and propagates toward the interior along the cleavages of muscovite. Kaolinite and muscovite occur as thick packets, being free of interlayering. Phase boundaries between both minerals show bidimensional crystallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…4). Another is the growth of kaolinite within muscovite during diagenesis, resulting in deformation and displacement of the topotactic mica template (Arostegui et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Another is the growth of kaolinite within muscovite during diagenesis, resulting in deformation and displacement of the topotactic mica template (Arostegui et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It might be postulated that the (0 0 1) face of the sheet silicate grain provides a suitable substrate, similar to that proposed for the growth of kaolinite within muscovite (Arostegui et al 2001). However, there are several problems with this.…”
Section: P±t Conditions Of Lens Growthmentioning
confidence: 94%
“…Kaolinite also partly replaces detrital muscovite laths, showing displacive precipitation along the cleavage planes, leading to "fanning" along the edges of the mica flakes (Fig. 4c, below centre) (De Ros, 1998;Arostegui et al, 2001). Accessory phases include scarce apatite and rutile.…”
Section: Y1(cordillera Oriental)mentioning
confidence: 99%
“…All these retrograde-diagenetic clay-minerals show a texture parallel or sub-parallel to the original metamorphic phyllosilicates. They are the result of epitaxial and/ or topotaxial reactions (e.g., Arostegui et al, 2001), therefore they inherit the same crystallographic orientation of the mother phases (Nieto et al, 1994; hence a distinction between metamorphic and retrograde phyllosilicates, based only on their orientation is impossible.…”
Section: Clay Mineral Reaction Progressmentioning
confidence: 99%
“…Banfield and Eggleton, 1990;Jiang and Peacor, 1991;Dong et al, 1998;Arostegui et al, 2001;Ece and Schroeder, 2007). Previous investigations revealed that micas can alter by weathering to both halloysite and kaolinite (e.g.…”
Section: Introductionmentioning
confidence: 99%